2020
DOI: 10.1016/j.ijom.2019.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of airway interventions and gastrostomy tube placement in infants with Robin sequence

Abstract: The purpose of this study was to evaluate feeding impairment following non-operative or operative management of airway obstruction in a large series of infants with Robin sequence (RS) by rate of G-tube placement. A retrospective study was conducted at Boston Children's Hospital including 225 patients (47.1% female) with RS treated between 1976 and 2018. Subjects were grouped by intervention required for successful management of airway obstruction: nonoperative only (n = 120), tongue-lip adhesion (TLA, n = 75)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In an earlier study, our own group also found a higher rate of gastrostomy tube insertion in individuals who had TLA than those with MDO. 24 As our group's earlier report of gastrostomy tube rates included significant sample overlap with this study, these findings suggest that use of gastrostomy tubes is a poor surrogate marker for feeding ability and weight gain; variables such as the interest of the surgical team to avoid feeding for some time in order to reduce dehiscence rates of TLA, among other factors, may influence feeding tube decisions.…”
Section: Discussionsupporting
confidence: 55%
“…In an earlier study, our own group also found a higher rate of gastrostomy tube insertion in individuals who had TLA than those with MDO. 24 As our group's earlier report of gastrostomy tube rates included significant sample overlap with this study, these findings suggest that use of gastrostomy tubes is a poor surrogate marker for feeding ability and weight gain; variables such as the interest of the surgical team to avoid feeding for some time in order to reduce dehiscence rates of TLA, among other factors, may influence feeding tube decisions.…”
Section: Discussionsupporting
confidence: 55%
“…Tongue-lip adhesion also has been correlated with delays in speech and language production. Our multidisciplinary team uses MDO to primary surgical treatment because it addresses a multifaceted dysfunction in the sequence 4,5,21 . Furthermore, studies have shown that this strategy has a lower cost burden to the system as well with estimated cost saving of US $300,000 over tracheostomy in a 3-year period and a lower cost than tongue-lip adhesion when associated procedures and outpatient care for PRS are taken into account 26 …”
Section: Discussionmentioning
confidence: 99%
“…The PRS sequence begins with the failure of the mandible to grow anteriorly (micrognathia), which reduces the oropharyngeal space 2 and causes posterior displacement of the tongue (glossoptosis) 3 leading to AO. Respiratory dysfunction due to AO is the main cause of feeding difficulties leading to poor growth 4–6 . Furthermore, PRS can present as one component of a known or suspected syndrome (syndromic PRS [sPRS]) or as an isolated finding (isolated PRS [iPRS]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the common symptoms appeared in patients with PRS. The causes of malnutrition in PRS are various, which may be related to the high energy consumption of respiratory work caused by upper airway obstruction, or to feeding difficulty (FD) caused by micrognathia and glossoptosis (8). The latter one may also be a direct result of respiratory dysfunction.…”
Section: Discussionmentioning
confidence: 99%